2016
DOI: 10.1103/physrevb.94.024107
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced mobility of small defect clusters in covalent materials

Abstract: Although defect clusters are detrimental to electronic and mechanical properties of semiconductor materials, annihilation of such clusters is limited by their lack of thermal mobility due to high migration barriers. Here, we find that small clusters in bulk SiC (a covalent material of importance for both electronic and nuclear applications) can become mobile at room temperature under the influence of electron radiation. So far, direct observation of radiationinduced diffusion of defect clusters in bulk materia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…For instance, Jiang et al [63] used accelerated molecular simulations to show that migration barrier for C tri-interstitial cluster is ~4.12 eV, which means that this cluster will be immobile on experimental time scales up to temperatures of 1,200K (at these temperatures the cluster performs ~ 1 hop/day). However, there is recent experimental evidence that under some irradiation conditions clusters in SiC can undergo radiation-induced diffusion due to ballistic collision of the incoming particles with cluster atoms [26]. This phenomenon has been discovered in SiC only recently and the effective migration barriers of clusters during irradiation of SiC are unknown.…”
Section: Effect Of Cluster Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Jiang et al [63] used accelerated molecular simulations to show that migration barrier for C tri-interstitial cluster is ~4.12 eV, which means that this cluster will be immobile on experimental time scales up to temperatures of 1,200K (at these temperatures the cluster performs ~ 1 hop/day). However, there is recent experimental evidence that under some irradiation conditions clusters in SiC can undergo radiation-induced diffusion due to ballistic collision of the incoming particles with cluster atoms [26]. This phenomenon has been discovered in SiC only recently and the effective migration barriers of clusters during irradiation of SiC are unknown.…”
Section: Effect Of Cluster Migrationmentioning
confidence: 99%
“…(a) shows a low angle annular dark field (LAADF) STEM image of Kr-irradiated 3C-SiC with the viewing direction along the <110> axis. Compared to high-angle annular dark field (HAADF) STEM images, LAADF images emphasize strain contrast, making small BSDs more visible[26]. The bright spots are the Si atom columns, as shown in the inset.…”
mentioning
confidence: 99%
“…The energy transferred from an incident electron to an atom in the sample, ′ , is given by, [37] ′ 1.02 496…”
Section: Stability Of La Vacancy In Lamno 3 During the Experimentsmentioning
confidence: 99%
“…Positive values of these quantities imply that the binding of an interstitial or a smaller cluster to another cluster is favored. Thus a cluster with positive binding energies is expected to grow under irradiation in the presence of a supersaturation of interstitials or mobile small clusters [46]. All compositions of SIA clusters reported in this study, except Si4, were found to have positive binding energies.…”
Section: Thermodynamic Stability Of Clustersmentioning
confidence: 85%